Advances in quantifying microbial contamination in potable water: Potential of fluorescence‐based sensor technology. (18th November 2022) - Gunter, Hannah; Bradley, Chris; Hannah, David M.; Manaseki‐Holland, Semira; Stevens, Rob; Khamis, Kieran
Abstract: Improved monitoring of potable water is essential if we are to achieve the UN Sustainable Development Goals (SDGs), specifically SDG6: to make clean water and sanitation available to all. Typically monitoring of potable water requires laboratory analysis to detect indicators of fecal pollution, such as thermotolerant coliforms (TTCs), Escherichia coli ( E. coli ), or intestinal enterococci. However, these analyses are time‐consuming and expensive, and recent advances in field deployable sensing technology offer opportunities to investigate both the spatial and temporal dynamics of microbial pollution in a more resolved and cost‐effective manner, thus advancing process‐based understanding and practical application for human health. Fluorescence offers a realistic proxy for monitoring coliforms in freshwaters with potential for quantification of potable water contamination in near real‐time with no need for costly reagents. Here, we focus on E. coli to provide a state‐of‐the‐art review of potential technologies capable of delivering an effective real‐time E. coli sensor system. We synthesize recent research on the use of fluorescence spectroscopy to quantify microbial contamination and discuss a variety of approaches (and constraints) to relate the raw fluorescence signal to E. coli enumerations. Together, these offer an invaluable platform to monitor drinking water quality which is required in situations where the water treatment and distribution infrastructure is degraded, for example in less economically developed countries; and during disaster‐relief operations. Overall, our review suggests that the fluorescence of dissolved organic matter is the most viable current method—given recent advances in field‐deployable technology—and we highlight the potential for recent developments to enhance approaches to water quality monitoring. This article is categorized under: Engineering Water > Water, Health, and Sanitation Engineering Water > Methods Human Water > Methods Abstract : Schematic illustrating the scope and inter‐connectivity of methods that can be used to measure E. coli in water.